O-GlcNAc: a bittersweet switch in liver - Kaisi eZhang; Ruonan eYin; Xiaoyong eYang (Frontiers in Endocrinology, 2014)
The liver is a vital organ responsible for maintaining nutrient homeostasis. After a meal, insulin stimulates glycogen and lipid synthesis in the liver; in the fasted state, glucagon induces gluconeogenesis and ketogenesis, which produce glucose and ketone bodies for other tissues to use as energy sources. These metabolic changes involve spatiotemporally coordinated signaling cascades. O-linked β-N-acetylglucosamine (O-GlcNAc) modification has been recognized as a nutrient sensor and regulatory molecular switch. This review highlights mechanistic insights into spatiotemporal regulation of liver metabolism by O-GlcNAc modification and discusses its pathophysiological implications in insulin resistance, non-alcoholic fatty liver disease, and fibrosis.